Carbon fractions and stock in response to solid and fluid organomineral fertilizers in highly fertile soils - Correa, Juliano Corulli; Rodio, Lauri Gaetano; Rigo, Amanda Zolet; Grohskopf, Marco Andre [UNESP]; Rebellatto, Agostinho; Mafra, Alvaro Luiz (Empresa Brasil Pesq Agropec, 2019)
The objective of this work was to evaluate the effect of the application of organomineral and mineral fertilizers to highly fertile soils on the carbon management index (CMI) and carbon fractions and stock. The experiment was carried out on an Oxisol and Inceptisol, under no-tillage, in three crop seasons. The treatments consisted of two organomineral fertilizers and of two mineral fertilizers in solid and fluid forms, besides a control without fertilization. The application of organomineral and mineral fertilizers, in solid and fluid forms, to the different soil classes with high fertility promoted changes in total organic carbon, particulate organic carbon, and carbon associated with minerals, as well as in carbon stocks and the CMI. In the treatments with fluid mineral fertilizer and solid organomineral fertilizer. such changes occurred only in the Inceptisol due to the lower degree of weathering of this soil. The higher values of the CMI, with the fluid mineral fertilizer in the Inceptisol, allow inferring on which would be the best management practice aiming at the increase and maintenance of carbon in the soil-plant system, based on the yield results of wheat, sorghum, and corn, which were similar to those obtained with the other fertilizers.
Keywords: fluid fertilizer; no-tillage; organomineral fertilizer